From The Editor (Health Education in Practice: Journal of Research for Professional Learning, 2019)
Welcome to Volume 2 of Health Education In Practice: Journal of Research for Professional Learning. As the journal enters its second year we look to the future of health education, with a focus on equipping our health workers for the future challenges facing the health workforce.